Poor Governance System in Nigeria: Can It Be Remedied Using the Yoruba Indigenous Governance Model? - Adegbami, Adeleke (Journal of Governance and Public Affairs, 2025)
The failure of successive governments to implement necessary measures to address numerous challenges facing the country has led to doubts about the capacity of the modern government system to solve Nigeria's basic problems. Therefore, this study examines the factors that contribute to the poor governance system, why successive Nigerian political leaders continue to perpetuate it, and how Yoruba's indigenous governance model can be used to address these issues. The data for this study are qualitative and sourced from secondary materials, including government official documents, official publications from international institutions and organizations, journals, newspapers, and online sources, analyzed through content analysis. The study applies Omoluabi's Integrity Theory to interpret the findings. Omoluabi embodies a well-mannered, intelligent, and dignified personality. Consequently, there is a connection between good governance and Omoluabi’s qualities, many of which are absent in successive Nigerian political leaders; they also lack problem-solving skills, leading to lax governance and its negative effects on Nigeria and its people. Yoruba indigenous governance approaches, such as the traditional judicial model of “serious oath-taking,” the prompt and appropriate sanctioning of offenders, the Yoruba checks and balances system, and security models, are essential for rebuilding Nigeria’s democratic governance foundation. The study concludes that Nigeria will not achieve a well-ordered society or good governance unless the Yoruba indigenous governance model is adopted and politicians and leaders embrace the attributes of Omoluabi.